Strategy for Developing the Existence of Caruban Baru Market in the Era of Society 5.0 - Maulidina Dwi Choirun Nisaa; Amin Wahyudi (Universitas Muhammadiyah Surabaya, 2023)
This research is discuss about the right inovation and solution for traditional market to maintain the existence in industrial revolutional era 4.0 and society 5.0 nowadays. the research method that used is qualitative method with descriptive research kind. Whereas the data collection technique that used was literature review, interview & observation. The result from this research is the strategy who can do to develop the existence of pasar caruban baru, that is to maintain bargaining transaction, increase quality of product for the whole commodity, increase the application of friendly market culture, provision of facilities from village government for developing knowledge & skill in using digital technology, utilize science & technology for larger marketing reach, innovation in promotion, creating digital market application, finding special interesting characteristic, improving market infrastructure, local government commitment about legacy to support market development, the government role in electronic facilities transaction. This research ecpected being one of local government reference to overcome decreasing the existence of Caruban Baru market.